TINGKAT KEPATUHAN PENARIK BECAK SUKA KARYA TERHADAP ATURAN ORGANISASI PERSATUAN BECAK SUKA KARYA (PBSK) KECAMATAN TAMPAN KOTA PEKANBARU - ", Hendri; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The goal of research is to find out how the compliance level of the rickshaw pullers Sukakarya forthe rules applied by the rickshaw union organizations Suka Karya(PBSK) and what factors affect the rickshaw pullers dutifully forthe existing rules. Research using quantitative methods by means of data capture all members of rickshaw pullers Like existing the way Sukakarya of Tampan Subdistrict of Pekanbaru City. To know the number of members of the rickshaw pullers that are on the road Suka Karya and to know clearly the number of respondents to the census method used in field is the entire population be made respondents. The field data into a population of 107 people towing pedicab so defined the overall respondents made samples. To collect data from respondents used the method of direct observations, interviews, and documentation, and data processing used for cuantitativemethod. This research see humans always want to meet his needs so that respondents who are members of the Organization of the pedicab in general have middle income and above so that the members of the rickshaw pullers have adequate income. Earning members of the rickshaw pullers Suka Karya strongly influenced the level of compliance of the agreed rules. Rickshaw Union Suka Karya members very comply with rules set forth the direction, so all the rules to become a benchmark in the members operate as rickshaw pullers. Members of the rickshaw pullers Suka Karya is always accountable to consumers and always keep the consumer satisfaction. Members of the rickshaw pullers sukakarya very rarely troubled with fellow members, consumers and also the leadership of the rickshaw pullers Suka Karya. The relationship of members with the leaders so close because the leadership is very open with members of the rickshaw pullers Suka Karya.Keywords: degree of Compliance, rules, Rickshaws.